Strategy for The Development of Culinary Sector Entrepreneurs in The Cipondoh Lake Tourism Destination, Tangerang Regency, Banten Province - Amrullah, Amrullah; Nurbaeti, Nurbaeti; Ratnaningtyas, Heny; Asmaniati, Fetty; Osman, Ismeth Emier (Institut Pariwisata Trisakti, 2024)
This study aims to determine the strategy for developing entrepreneurship in the culinary field in the tourist area of ​​Lake Cipondoh. This type of research uses a qualitative description with the SWOT analysis method with observations and interviews with entrepreneurs in the culinary field at Lake Cipondoh. The results showed that the primary strategy produced was the SO strategy, with the highest score of 3.44 in quadrant I. The culinary entrepreneur development strategy at Lake Cipondoh can be implemented with the SO strategy program, namely: (1) a varied food menu; (2) Doing promotions on social media; (3) Increasing the number of employees on weekends; (4) Providing promotions or discounts. It is hoped that food stalls in Lake Cipondoh will continue to innovate in improving the quality of their products and promoting them on social media. The Tangerang City Government is expected to train managers and entrepreneurs on the quality of human resources for creating websites and social media promotions and organizing certain events at Lake Cipondoh. Keywords: SWOT analysis, entrepreneurs, culinary sector